2021
DOI: 10.1002/14651858.cd013503.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Enteral tube feeding for people with severe dementia

Abstract: Davies 2014Davies N, Maio L, Rait G, Ili e S. Quality end-of-life care for dementia: what have family carers told us so far? A narrative synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 147 publications
(15 reference statements)
0
25
0
2
Order By: Relevance
“…Prior research suggested that feeding tubes did not confer survival benefit, but the certainty of evidence was low because of risk of selection bias and limited controlling for confounders. 7,15 The current study found a lack of survival benefit with NGF compared with CHF and attempted to reduce risk of bias by selecting hospitalized patients with indication for tube feeding due to feeding problems and excluded patients with existing feeding tubes. We also controlled for a wide range of potential confounders through comprehensive review of hospital paper charts and the electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research suggested that feeding tubes did not confer survival benefit, but the certainty of evidence was low because of risk of selection bias and limited controlling for confounders. 7,15 The current study found a lack of survival benefit with NGF compared with CHF and attempted to reduce risk of bias by selecting hospitalized patients with indication for tube feeding due to feeding problems and excluded patients with existing feeding tubes. We also controlled for a wide range of potential confounders through comprehensive review of hospital paper charts and the electronic medical record.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A recent Cochrane review found a high risk of bias due to confounding and selection bias among existing controlled, nonrandomized studies. 15 Critics challenged whether patients on tube feeding and those on oral feeding are comparable groups as the oral feeding patients may not have an indication for tube feeding. 14,15 Furthermore, the majority of studies were on percutaneous endoscopic gastrostomy (PEG) feeding or did not differentiate between nasogastric tube feeding (NGF) and PEG feeding.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the Japanese population, half of the patients who qualified for PEG were at least 80 years old ( 15 ). In a retrospective study on hospitalized patients, the number of PEGs in the elderly (more than 65 years) increased in the United States from 1993 to 2003 ( 33 ). However, more recent data presented decreasing trend in patients with neurodegenerative disorders ( 34 ).…”
Section: Discussionmentioning
confidence: 99%